Vascular wall hypoxia promotes arterial thrombus formation via augmentation of vascular thrombogenicity - Matsuura, Yunosuke; Yamashita, Atsushi; Iwakiri, Takashi; Sugita, Chihiro; Okuyama, Nozomi; Kitamura, Kazuo; Asada, Yujiro (Thrombosis and Haemostasis, 2015)
Atherosclerotic lesions represent a hypoxic milieu. However, the significance of this milieu in atherothrombosis has not been established. We aimed to assess the hypothesis that vascular wall hypoxia promotes arterial thrombus formation. We examined the relation between vascular wall hypoxia and arterial thrombus formation using a rabbit model in which arterial thrombosis was induced by 0.5 %- cholesterol diet and repeated balloon injury of femoral arteries. Vascular wall hypoxia was immunohistochemically detected by pimonidazole hydrochloride, a hypoxia marker. Rabbit neointima and THP-1 macrophages were cultured to analyse prothrombotic factor expression under hypoxic conditions (1 % O2). Prothrombotic factor expression and nuclear localisation of hypoxia-inducible factor (HIF)-1α and nuclear factor-kappa B (NF-κB) p65 were immunohisto-chemically assessed using human coronary atherectomy plaques. Hypoxic areas were localised in the macrophage-rich deep portion of rabbit neointima and positively correlated with the number of nuclei immunopositive for HIF-1α and NF-κB p65, and tissue factor (TF) expression. Immunopositive areas for glycoprotein IIb/IIIa and fibrin in thrombi were significantly correlated with hypoxic areas in arteries. TF and plasminogen activator inhibitor-1 (PAI-1) expression was increased in neointimal tissues and/or macrophages cultured under hypoxia, and both were suppressed by inhibitors of either HIF-1 or NF-κB. In human coronary plaques, the number of HIF-1α-immuno-positive nuclei was positively correlated with that of NF-κB-immuno-positive nuclei and TF-immunopositive and PAI-1-immunopositive area, and it was significantly higher in thrombotic plaques. Vascular wall hypoxia augments the thrombogenic potential of atherosclerotic plaque and thrombus formation on plaques via prothrombotic factor upregulation.
Keywords: Atherothrombosis; hypoxia; hypoxia-inducible factor-1; nuclear factor-κB; tissue factor